Depression and Anxiety Levels Increase Chronic Musculoskeletal Pain in Patients with Alzheimer's Disease - Tsatali, Marianna; Papaliagkas, Vasileios; Damigos, Dimitrios; Mavreas, Venetsanos; Gouva, Maria; Tsolaki, Magda (Current Alzheimer Research, 2014)
Background/Objectives: During the next decades a rapid increase is expected in the number of patients with dementia suffering from pain who often take less medication compared to normal elderly, due to several diagnostic barriers. Comorbid mood disorders result in great difficulties in pain assessment and further treatment. Design: Twenty five patients with Alzheimer’s disease, comorbid mood disorders, and chronic musculoskeletal pain (experimental group) and thirty one patients with Alzheimer’s disease and chronic musculoskeletal pain without comorbid mood disorders (control group) were examined. The assessment tools used were Geriatric Pain Measure, Patient Health Questionnaire, Pain Assessment in Advanced Dementia, Mini Mental State Examination and Pain Anxiety Symptom Scale. Statistical analysis was performed by SPSS v17.0, using the Pearson correlation and the multiple linear regression analysis. Results: The correlation between mood disorders and levels of pain intensity in the experimental group was found to be statistically higher than that in the control group (p< .001). Among all quantitative variables, highly significant correlation (p< .001) was observed between stress and depression symptomatology (r =.550, p<.001) in the experimental group. Normal regression analysis was used to assess possible differences between demographic data and PASS scores. Scores in fearful thinking and physiological responses scales of PASS were higher in female than male (p=.014), whereas scores in the cognitive anxiety scale of PASS have shown a highly significant positive correlation with years of education (p< .001). Discussion: It seems that depression and anxiety are associated with chronic musculoskeletal pain intensity in dementia, thus need to be taken into consideration by health professionals for patient’s management.
Keywords: pain